Mechanism Behind the Easy Exfoliation of Ga2O3 Ultra‐Thin Film Along (100) Surface. Issue 5 (2nd January 2019) - Barman, Sajib K.; Huda, Muhammad N.
Abstract : The transparent wide band gap semiconductor β ‐Ga2 O3 has gained wide attention due to its suitability to a wide range of applications. Despite not being a van der Waals material and having highly strong ionic bonding, the material can be mechanically cleaved and exfoliated easily along favorable surfaces to make ultra‐thin layers and used in device fabrications. One of the interesting properties of this material is that thin layers preserve the pristine bulk‐like electronic properties, which makes it even more promising for applications in power devices. However, very little is known about the mechanism why such ultra‐thin film or even single bilayer exfoliation is favorable from the bulk. In this letter, we have explained the mechanism of such phenomenon by detailed analyses of different types of Ga–O bonding character. The protocol of methodology used and developed in this study can be utilized in general to understand bond breaking and forming of other complex materials as well. This understanding will give us a better control to fabricate thin film 2D devices. Abstract : Despite not being a van der Waals material, it is known that thin film exfoliation in β ‐Ga2 O3 along (100) surface is as easy as like peeling graphene with a scotch tape. This characteristic is attributed to the stronger Ga–O tetrahedral bonds over relatively weaker octahedral counterparts. The weaker octahedral bonding also has some anti‐bonding character.